CLINICAL INFORMATIVE VALUE IN THE DIAGNOSTIC TESTING FOR DETECTION OF ROTAVIRUS INFECTIONS IN ADULT PATIENTS WITH ACUTE DIARRHEA - E. A. Kozhukhova; I. V. Gorbova; N. V. Andreeva; V. D. Ivashchenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2018)
The paper suggests the results of retrospective cohort study. We analyzed the results of clinical and laboratory examination of 102 hospitalized adult patients with acute diarrhea (AD) of moderate severity and positive feces test for rotavirus. Specific examination for the detection of various pathogens of AD along with standard cultural, serologic (based on the determination of specific antibodies) and ELISA methods included the study of the patient’s feces by PCR. It was found that the use of a complex of modern methods of specific diagnosis allows in 67.2% of individuals along with markers of rotavirus simultaneously identify markers of other pathogens, including bacterial – 51% of patients. Among the examined persons hospitalized on the 4th day of the disease and later, there are 2 times more patients with concomitant diseases of the gastrointestinal tract and 2.4 times more patients taking antimicrobial drugs at the prehospital stage than among those who admitted for the 1st three days of the disease. The cases in adult patients with concomitant non-infectious pathology of the gastrointestinal tract compared to those without it turned to be significantly rarer simultaneously positive for rotavirus and Campylobacter spp. In the examined patients with colitis syndrome there is an apparent trend of more frequent detection of a positive cultural test for Salmonella spp. In the absence of markers of bacterial enteropathogens in the clinical material in the group of adult patients with only detected rotavirus, colitis syndrome is documented 2 times more often than in patients with a positive combined reaction to rota- and norovirus.